Cyber Security and Critical Infrastructures 2nd Volume - Maglaras, Leandros; Janicke, Helge; Ferrag, Mohamed Amine (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The second volume of the book contains the manuscripts that were accepted for publication in the MDPI Special Topic "Cyber Security and Critical Infrastructure" after a rigorous peer-review process. Authors from academia, government and industry contributed their innovative solutions, consistent with the interdisciplinary nature of cybersecurity. The book contains 16 articles, including an editorial that explains the current challenges, innovative solutions and real-world experiences that include critical infrastructure and 15 original papers that present state-of-the-art innovative solutions to attacks on critical systems.